Financial planning models : construction and use - Kaye, G. Roland (London : Academic Press, 1994)
Introduction. Alternative views of financial planning. Types of models - structures and examples. Life cycle of a model. Building a model. Other models. Modelling and decision support systems...
Keywords: Finance; Business enterprises; Corporations; Corporations -- Finance; Business enterprises -- Finance